2019
DOI: 10.5114/biolsport.2019.81112
|View full text |Cite
|
Sign up to set email alerts
|

Exploring possible relationships between 25(OH)D deficiency and variables related to inflammation, endothelial function, and enzymatic antioxidants in adolescent athletes: a prospective study

Abstract: Although the role of vitamin D in calcium and bone metabolism is well documented, there is little clarity regarding the implications of low vitamin D status for inflammation, endothelial function, and antioxidant status in adolescent athletes. A prospective cohort study was conducted, and 44 male adolescent athletes, training at a sports academy in the Middle East, were assigned to either the intervention group (VitDs), consisting of vitamin D deficient athletes [twenty-five hydroxyvitamin D (25(OH)D) <20 ng/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In our study, the prevalence rate of inadequate vitamin D supply (51.4%) correlated closely with the metaanalysis recently published by Farrokhyar et al [46], in which 56% of the athletes examined worldwide showed inadequate vitamin D supply (< 30 ng/ml). The prevalence of inadequate vitamin D supply in other studies [25, 26, 28, 31] ranged from 51% -91, 3% of the athletes, with the average vitamin D value of the athletes (N=20969) in these studies ranging from 11,62 ± 9,24 ng/ml -38,45 ± 16,65 ng/ml [23][24][25][26][28][29][30][31][32][33]. The average vitamin D value of the study with most participants (N=18883) correlated with 29 ± 8 ng/ml [33] and the value of the Swiss Olympic athletes (N=651) with 30.32 ± 9.24 ng/ml [25] closely correlated with the average value in our study (N=111): 31.06 ± 10.61 ng/ml.…”
Section: Vitamin Dmentioning
confidence: 82%
“…In our study, the prevalence rate of inadequate vitamin D supply (51.4%) correlated closely with the metaanalysis recently published by Farrokhyar et al [46], in which 56% of the athletes examined worldwide showed inadequate vitamin D supply (< 30 ng/ml). The prevalence of inadequate vitamin D supply in other studies [25, 26, 28, 31] ranged from 51% -91, 3% of the athletes, with the average vitamin D value of the athletes (N=20969) in these studies ranging from 11,62 ± 9,24 ng/ml -38,45 ± 16,65 ng/ml [23][24][25][26][28][29][30][31][32][33]. The average vitamin D value of the study with most participants (N=18883) correlated with 29 ± 8 ng/ml [33] and the value of the Swiss Olympic athletes (N=651) with 30.32 ± 9.24 ng/ml [25] closely correlated with the average value in our study (N=111): 31.06 ± 10.61 ng/ml.…”
Section: Vitamin Dmentioning
confidence: 82%